Farmers’ Challenges in Mentha Cultivation: A Regional Perspective - Ajeet Kumar Bajpai; Sunil Kumar; Aman Verma; Akanksha Singh; G.P. Singh; Ravi Shankar (The Bioscan, 2025)
Mentha, or mint is a valuable aromatic and therapeutic crop that has important agricultural and economic implications. However, growing it presents a number of region-specific challenges for farmers, endangering both sustainability and profitability. In addition to economic problems like price volatility and high input costs, this review highlights important agronomic challenges like soil salinity, water scarcity, and pest outbreaks. These challenges are made worse by technological obstacles, such as a lack of mechanization and a sluggish adoption of sophisticated farming methods. Mentha production is further impacted by environmental factors like climate variability and diminishing water supplies, and farmer resilience is hampered by a lack of policy support and poor agricultural extension services. We suggest implementing technological advancements like integrated pest management, effective irrigation systems, and drought-resistant cultivars to address these issues. Farmers can be empowered through government initiatives like increased subsidies and equitable pricing structures, as well as strengthened extension services and training initiatives. Resilience also depends on sustainable practices like organic farming and water conservation. The necessity of all-encompassing approaches to guarantee sustainable mentha cultivation is highlighted by this review.